Glucocorticoids and Glucocorticoid-Induced-Leucine-Zipper (GILZ) in Psoriasis - Sevilla, Lisa M.; Pérez, Paloma (Frontiers in Immunology, 2019)
Psoriasis is a prevalent chronic inflammatory human disease initiated by impaired function of immune cells and epidermal keratinocytes, resulting in increased cytokine production and hyperproliferation, leading to skin lesions. Overproduction of Th1- and Th17- cytokines including interferon (IFN)-, tumor necrosis factor (TNF)-, interleukin (IL)-23, IL-17, and IL-22, is a major driver of the disease. Glucocorticoids (GCs) represent the mainstay protocol for treating psoriasis as they modulate epidermal differentiation and are potent anti-inflammatory compounds. The development of safer GC-based therapies is a high priority due to potentially severe adverse effects associated with prolonged GC use. Specific efforts have focused on downstream anti-inflammatory effectors of GC-signaling such as GC-Induced-Leucine-Zipper (GILZ), which suppresses Th17 responses and antagonizes multiple pro-inflammatory signaling pathways involved in psoriasis, including AP-1, NF-B, STAT3 and ROR-t. Here we review evidence regarding defective GC signaling, GC receptor (GR) function, and GILZ in psoriasis. We discuss seemingly contradicting data on the loss- and gain-of-function of GILZ in the imiquimod-induced mouse model of psoriasis. We also present potential therapeutic strategies aimed to restore GC-related pathways.